Religiusitas dan penyesuaian diri siswa (SUKMA : Jurnal Penelitian Psikologi, 2022)
The success of face-to-face learning is determined by students' self-adjustment. This study was conducted to determine the correlation between religiosity and student adjustment while undergoing limited face-to-face learning in the era of the covid-19 pandemic. The sample of this study were students who underwent limited PTM. The sampling technique used a purposive sampling model using a Likert scale data collection method. The measuring instrument used is a scale of religiosity and student adjustment. The data analysis process uses Spearman's Rho with the application of SPSS (Statistical Product and Service Solution) for Windows 25. The correlation coefficient score is 0.733 with a value of p = 0.000 (p < 0.01) indicating a very significant positive relationship between the two variables. This means that the higher the level of religiosity, the higher the student's self-adjustment, and vice versa. Thus, this study shows that the hypothesis is accepted. Keberhasilan pembelajaran tatap muka ditentukan oleh penyesuaian diri siswa. Penelitian ini dilakukan guna mengetahui korelasi antara religiusitas dengan penyesuaian diri siswa saat menjalani pembelajaran tatap muka terbatas di era pandemi covid-19. Sampel penelitian ini adalah siswa yang menjalani PTM terbatas. Teknik sampling menggunakan model purposive sampling dengan menggunakan metode pengumpulan data skala model Likert. Alat ukur yang digunakan adalah skala religiusitas dan penyesuaian diri siswa. Proses analisa data menggunakan Spearman’s Rho dengan aplikasi SPSS (Statistical Product and Service Solution) for windows 25. Dengan hasil skor correlation Coefficient sebesar 0,733 dengan nilai p = 0,000 (p < 0,01) menandakan adanya hubungan positif yang sangat signifikan antara kedua variabel. Artinya semakin tinggi individu memiliki tingkat religiusitas maka semakin tinggi penyesuaian diri siswa, begitu pula sebaliknya. Dengan begitu penelitian ini menunjukkan, bahwa hipotesis yang diajukan diterima.